Raising Pragmatics Awareness: How to Raise Conversational Implicature Awareness through Movies - Nurdiana Nurdiana (Journal of English Language and Culture, 2017)
Learning a language is not merely learning its grammar. There are some other factors which should be covered in language learning, e.g. language in use, or meaning and communication. In other words, L2 learners of English not only need to reach grammar competence, but also pragmatic competence. Unfortunately, pragmatic competence is rather neglected as language learning and teaching, most of the time, puts emphasis on grammar competence. Hence, in this paper, I would like to discuss the importance of integrating pragmatic competence, in this case, conversational implicature, in English language teaching and learning materials. A previous study, conducted by Manowong (2011), reported that non-native speakers of English have difficulty in interpreting conversational implicature. Thus, teachers should make great efforts to help the learners raise their conversational implicature awareness. One of the most effective ways to raise learners’ awareness on conversational implicature is by making use of authentic materials. Movies could be great sources to help learners raise their conversational implicature awareness. Therefore, in this paper, I would like to propose a model of materials which integrate some scenes of a movie that might be useful for teachers and learners in English language learning and teaching.  Keywords: Raising pragmatics awareness, conversational implicature, movies